Novel, emerging and provisional renal entities: The Genitourinary Pathology Society (GUPS) update on renal neoplasia - Trpkov, Kiril; Williamson, Sean R; Gill, Anthony J; Adeniran, Adebowale J; Agaimy, Abbas; Alaghehbandan, Reza; Amin, Mahul B; Argani, Pedram; Chen, Ying-Bei; Cheng, Liang; Epstein, Jonathan I; Cheville, John C; et al. (Modern pathology, 2021)
The Genitourinary Pathology Society (GUPS) undertook a critical review of the recent advances in renal neoplasia, particularly focusing on the newly accumulated evidence post-2016 World Health Organization (WHO) classification. In the era of evolving histo-molecular classification of renal neoplasia, morphology is still key. However, entities (or groups of entities) are increasingly characterized by specific molecular features, often associated either with recognizable, specific morphologies or constellations of morphologies and corresponding immunohistochemical profiles. The correct diagnosis has clinical implications leading to better prognosis, potential clinical management with targeted therapies, may identify hereditary or syndromic associations, which may necessitate appropriate genetic testing. We hope that this undertaking will further facilitate the identification of these entities in practice. We also hope that this update will bring more clarity regarding the evolving classification of renal neoplasia and will further reduce the category of "unclassifiable renal carcinomas/tumors". We propose three categories of novel entities: (1) "Novel entity", validated by multiple independent studies; (2) "Emerging entity", good compelling data available from at least two or more independent studies, but additional validation is needed; and (3) "Provisional entity", limited data available from one or two studies, with more work required to validate them. For some entities initially described using different names, we propose new terminologies, to facilitate their recognition and to avoid further diagnostic dilemmas. Following these criteria, we propose as novel entities: eosinophilic solid and cystic renal cell carcinoma (ESC RCC), renal cell carcinoma with fibromyomatous stroma (RCC FMS) (formerly RCC with leiomyomatous or smooth muscle stroma), and anaplastic lymphoma kinase rearrangement-associated renal cell carcinoma (ALK-RCC). Emerging entities include: eosinophilic vacuolated tumor (EVT) and thyroid-like follicular renal cell carcinoma (TLFRCC). Finally, as provisional entities, we propose low-grade oncocytic tumor (LOT), atrophic kidney-like lesion (AKLL), and biphasic hyalinizing psammomatous renal cell carcinoma (BHP RCC).
Keywords: lidé; nádory ledvin; Kidney Neoplasms; Humans